Heme Oxygenase-1 at the Nexus of Endothelial Cell Fate Decision Under Oxidative Stress - Raghunandan, Sindhushree; Ramachandran, Srinivasan; Ke, Eugene; Miao, Yifei; Lal, Ratnesh; Chen, Zhen Bouman; Subramaniam, Shankar (Frontiers in Cell and Developmental Biology, 2021)
Endothelial cells (ECs) form the inner lining of blood vessels and are central to sensing chemical perturbations that can lead to oxidative stress. The degree of stress is correlated with divergent phenotypes such as quiescence, cell death, or senescence. Each possible cell fate is relevant for a different aspect of endothelial function, and hence, the regulation of cell fate decisions is critically important in maintaining vascular health. This study examined the oxidative stress response in human ECs at the boundary of cell survival and death through longitudinal measurements, including cellular, gene expression and perturbation measurements. 0.5 mM hydrogen peroxide (HP) produced significant oxidative stress, placed the cell at this junction, and provided a model to study the effectors of cell fate. The use of systematic perturbations and high-throughput measurements provide insights into multiple regimes of the stress response. Using a systems approach, we decipher molecular mechanisms across these regimes. Significantly, our study shows that heme oxygenase-1 (HMOX1) acts as a gatekeeper of cell fate decisions. Specifically, HP treatment of HMOX1 knockdown cells reversed the gene expression of about 51% of 2892 differentially expressed genes when treated with HP alone, affecting a variety of cellular processes, including anti-oxidant response, inflammation, DNA injury and repair, cell cycle and growth, mitochondrial stress, metabolic stress and autophagy. Further analysis revealed that these switched genes were highly enriched in three spatial locations viz., cell surface, mitochondria, and nucleus. In particular, it revealed the novel roles of HMOX1 on cell surface receptors EGFR and IGFR, mitochondrial ETCs (MTND3, MTATP6), and epigenetic regulation through chromatin modifiers (KDM6A, RBBP5, and PPM1D) and long non-coding RNA in orchestrating the cell fate at the boundary of cell survival and death. These novel aspects suggest that HMOX1 can influence transcriptional and epigenetic modulations to orchestrate oxidative stress response affecting cell fate decisions.